Violation of Hemispheric Symmetry in Integrated Poynting Flux via an Empirical Model. Issue 4 (11th February 2022) - Cosgrove, Russell B.; Bahcivan, Hasan; Chen, Steven; Sanchez, Ennio; Knipp, Delores
Abstract: For southward interplanetary magnetic field (IMF) during local summer, the hemispherically integrated Poynting flux estimated by FAST‐satellite‐derived empirical models is significantly larger for the northern hemisphere (NH) than for the southern hemisphere (SH). In order to test whether the difference is statistically significant, the model uncertainties have been estimated by dividing the data sets for each hemisphere into two nonintersecting sets, and separately constructing the model using each of the four sets. The model uncertainty appears to be smaller than the estimated asymmetry. The asymmetry is mostly absent when the IMF is northward, except there is some evidence that it may actually reverse during local winter. The phenomena is coupled with what appears to be a more distinct two‐cell convection pattern in the NH, and a possibly greater cusp contribution in the SH. All this suggests an effect of magnetosphere‐ionosphere‐thermosphere coupling, probably related to asymmetries in Earth's geomagnetic field. Plain Language Summary: Energy enters Earth's atmosphere in various forms, including sunlight, fast‐moving particles, and also relatively low‐frequency electric and magnetic fields. The later component is referred to as Poynting flux (PF), and is important to study because it produces density anomalies that can perturb satellite orbits in unexpected ways. PF is produced by a complex interaction of Earth's geomagnetic field and particle‐populations with the solar wind coming from the sun, and is thus quite difficult to model through first principles physics. Data‐based models of PF, known as empirical models, can be used to produce a sort of ground‐truth for development and testing of the physics‐based models, which demonstrate our understanding of the phenomenon, and which will eventually be needed to develop a predictive capability. A particularly useful feature in this regard is the symmetry, or lack thereof, between Earth's northern and southern hemispheres. The difference between the hemispheres is relatively subtle, and so successfully modeling the difference using first‐principles physics would be a significant demonstration of understanding. In this work we provide an empirical assessment of the hemispheric symmetry of PF that can be used to provide such a discriminator. Key Points: Empirical models of Poynting flux are separately constructed for the northern and southern hemispheres using satellite data During local summer under active conditions, the northern hemisphere supports about 30% more total Poynting flux The most likely cause is the asymmetry in the geomagnetic field, which provides about 30% more conductance in the northern hemisphere